Virtual R&D teams definition - Ale Ebrahim, N. (aleebrahim.com, 2012)
Introduction: The literature related to virtual R&D teams reveals a lack of depth in the definitions (Ale Ebrahim et al., 2010). Although virtual teamwork is a current topic in the literature concerning global organizations, it is problematic to define the meaning of 'virtual teams' across multiple institutional contexts (Chudoba et al., 2005). The concept of a "team" is described as a small number of people with complementary skills who are equally committed to a common purpose, goal, and working approach for which they hold themselves mutually accountable (Zenun et al., 2007). It is worth mentioning that virtual teams (VTs) are often formed to overcome geographical or temporal separations (Cascio and Shurygailo, 2003). VTs work across boundaries of time and space using modern computer-driven technologies (Ebrahim et al., 2010). The term "VTs" is used to cover a wide range of activities and forms of technology-supported working (Anderson et al., 2007).